Extracción de colágeno a partir de escamas de peces de río por hidrólisis mixta - Aibar Inchaustegui, Mayra Abigail (2023)
The Amazon and the great biodiversity it possesses, makes industry and academia look for strategies to bring beneficial products to the market for human health. Artisanal fishing is one of the main economic activities in our region, and generates waste such as skin, scales, bones, etc., which are not used profitably. In this sense, the research sought to extract type I collagen from scales of Prochilodus nigricans (Boquichico), and Megaleporinus trifasciatus (Lisa), in order to give added value to the waste generated, reducing environmental pollution, and giving a source for the development of nutraceutical products. The study was of an experimental type, a factorial design with levels was used, applying a completely randomized design (DCA). Extraction was by mixed hydrolysis, using acetic acid and pepsin at temperatures of 15 and 20 °C for extraction. The collagen obtained was characterized by protein content and Fourier transform infrared spectrophotometry – FTIR. The results show that the collagen extracted from Lisa scales at a temperature of 15°C has the highest protein percentage of 26.68 ± 1.08%. When analyzing the structure of collagen, by means of FT-IR, the data of the detected bands of collagen from river fish scales coincide with the data of the standard sample, absorption bands that correspond to the characteristic peptide bond of type I collagen Concluding that it is possible to extract collagen type I from flakes of Amazonian hydrobiological species, for its subsequent application in the medical, pharmaceutical and food industry.